Local recovery of the compressional and shear speeds from the hyperbolic DN map. (12th December 2017) - Stefanov, Plamen; Uhlmann, Gunther; Vasy, Andras
Abstract: We study the isotropic elastic wave equation in a bounded domain with boundary. We show that local knowledge of the Dirichlet-to-Neumann map determines uniquely the speed of the p-wave locally if there is a strictly convex foliation with respect to it, and similarly for the s-wave speed.